The Feasibility of Using UAV Structure from Motion Photogrammetry to Extract HBIM of the Great Ziggurat of UR - Sarhan, Hussein R; Abed, Fanar M. (Iraqi Journal of Science, 2021)
Culture heritage reflects nation’s legacy and therefore should be protected from damage in order to pass it to future generations. Recently, such protection can be applied by 3D digitization techniques such as conservation, restoration, documentation, etc. The 3D digitalization of heritage assets has encountered numerous focus in the last two decades due to the development in data capturing techniques and technological advancement in 3D remote sensing (RS) approaches such as photogrammetry and laser scanning. However, the abundance of 3D information resources and spatial data modelling and analysis methods have urged stakeholders to adopt intelligent 3D data management system so called Building Information Modelling (BIM) to facilitate data approaching and management. Historic Building Information Model (HBIM) is a special case of the BIM system, however it reflects the possibility to apply the BIM technology to the historical and heritage buildings. In this research, Structure from motion (SfM) photogrammetric routine based on Unmanned Aerial Vehicles (UAVs) images was applied to build HBIM of the Great Ziggurat of Ur in the south of Iraq. Based on the 3D geometric and texturing information extracted through photogrammetry and the historical information provided, virtual reconstruction has been carried out using (HBIM) technology. This was achieved by applying realistic materials and texturing information in order to document the building, which is directed to investigate the feasibility of implementing image-based 3D modelling within HBIM environments. Restoring the missing parts of the Ziggurat temple was also a focus of this research by implementing reverse engineering methodologies based on available information considered within the extracted HBIM. This can successfully represent a complete virtual reality model and a management information system of the Ziggurat building to be passed to future generations. The work also includes data assessment and validation with the as-built model generated from reference measurements within Computer Aided Design (CAD) environment.